A Varied Presentation of Tuberous Sclerosis - Dhungana, Saraswoti; Chapagain, Manisha; Taluchan, Pratikchya; Dangol, Kabin Man (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 88-90 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8818